DIAMETER DAN DIMENSI PARTISI PADA GRAF CATERPILLARS - Margaretha Dwi Cahyani (Universitas Katolik Widya Mandala Surabaya Kampus Kota Madiun, 2015)
Suppose G=(V,E) is connected graph and u,v Î V are any two points in G . Diameter G is defined as the maximum distance between two points in G, denoted by diam (G) = maxd(u,v)|u,vÎV(G). Diameter of Caterpillars Graph (Cn,m) is diam(Cn,m) = n + 1. Suppose there is a point v in G. Then the representation v to P is defined as r(v|P = (d(v,S1), d(v,S2), d(v,S3), ..., d(v,Sk)). If any different point in G has a different representation of the P, then P is called the resolving partition. The minimum cardinality of k-resolving partition against V(G) referred to the partition dimension of G, denoted by pd(G). Partition dimension of graph Caterpillars (Cn,m) is pd(Cn,m) = n.m + 1 Key Words: Caterpillars Graph, Diameter Graph, Partition Dimension, Resolving Partition.